Pilgrimage and Environment in South India: A Research of Compatibility Between Conflicting Ideologies - Mr. Rmy Delage
The thorough study of the spatial insertion of a huge pilgrimage, well known all over South India as Sabarimala Yatra in Kerala, in which the male members of the Hindu community form the core of the participants, provides exiting research material. A geographical analysis of this gathering related to the cult of Ayyappa, an ambivalent deity typical of that area, sheds indeed some light on the nature of links entertained between the multifaceted phenomenon of religious travel (pilgrimage) and the reflexive notions of territoriality and territory. Beyond the relevance of studying pilgrimage as a geographical ritual and phenomena, I propose here to deconstruct the pilgrimage though the analysis of the main discourses, which preside over the management of environmental issues and the refashioning of both cultural and regional identity. This presentation aims at bringing fresh inputs regarding the debate around nature and culture as each of these ideologies tends to favour one of the components of this dialectic or deny all of them. Let's remind that the Sabarimala temple, which is the final and central link of a long chain of ritual places to be crossed by pilgrims before reaching it, is located in the PeriyarTiger Reserve (PTR) in Kerala, thus reinforcing tensions between the Kerala Forest Department and the TDB because the latter is constantly breaking environmental laws such as the Forest Conservation Acts (among many others) by cutting trees and misappropriating lands. The hidden objective of the TDB is to may their hands on more and more lands to build a new temple town contributing then to the destruction not only of the geographical and ritual networks of pilgrimage at the regional scale but also of the religious spirit which presides over this temple